Lessons from the Field: Advancing Micro-hydro Initiatives for Community-Based Sustainable Forest Management - Nugroho, Hunggul Yudono Setio Hadi; Wahyuningrum, Nining; Setiawan, Ogi; Isnan, Wahyudi; Auliyani, Diah; Hanindityasari, Luthfi (International Journal of Sustainable Energy Planning and Management, 2026)
For forest-dependent communities, especially in the global South, one of the major issues is access to clean and reliable energy. On the other hand, ongoing forest degradation driven by unsustainable practices and pressures of climate change poses a high risk to the important watershed function to support community resilience. This study investigates the role of Micro-Hydro Power Plants (MHPPs) as incentive-based instruments within Community-Based Sustainable Forest Management (CBSFM) frameworks. The research methodology is structured into three key phases: (1) identification and spatial mapping of MHPP initiatives; (2) classification of projects based on physical, socio-economic, and institutional attributes; and (3) analysis and synthesis to identify critical success factors and potential barriers. The study shows that key success factors include active community engagement, the implementation of Payment for Watershed Ecosystem Services (PWES) schemes, and a metaphorical “perpetual motion” approach, where initial external support is gradually replaced by community-based self-management. Challenges such as technical constraints, environmental risks, and social dynamics are also discussed, along with solution-oriented approaches through participatory planning, data-driven site selection, and strengthening local institutions. This article provides practical guidance for policy makers and field actors in integrating energy access, forest conservation, and sustainable rural development through an adaptive and locally based ecosystem approach.